Analisis Perbandingan Model Desain Pembelajaran ADDIE dan Dick & Carey dalam Pengembangan Pembelajaran - Amriyah, Chairul; Andrini, Mike; Sutriani, Ikat; Kurniawati, Elly; Prasetyo, Nabil Tito; Jatmiko, Agus; Meriyati, Meriyati (Paedagogie, 2026)
This study is motivated by the limited number of studies that specifically analyze the comparison between the ADDIE instructional design model and the Dick & Carey model, even though both models play an important role in improving the quality of instructional planning. This study aims to analyze and compare the characteristics, development stages, and advantages of the two instructional design models in the development of learning. This study uses a qualitative approach with a library research method. Data were obtained from various scientific literature sources such as books, journals, research articles, and academic documents that discuss instructional design models. The collected data were then analyzed using descriptive qualitative analysis with a comparative approach to identify the similarities and differences between the ADDIE model and the Dick & Carey model. The results of the study show that both models apply a systematic approach in designing instruction, but they differ in terms of complexity and development structure. The ADDIE model has five main stages that are flexible and relatively simple, making it easier to apply in various learning contexts. Meanwhile, the Dick & Carey model consists of ten more detailed and comprehensive stages and emphasizes the integration of learning objectives, instructional strategies, materials, and evaluation. This study concludes that the selection of an instructional design model needs to be adjusted to the objectives and the complexity of the learning being designed. The findings of this study are expected to provide a theoretical contribution to the study of instructional design and serve as a practical reference for educators in selecting an appropriate instructional design model. Future research is recommended to conduct empirical studies to test the effectiveness of both models in classroom learning practices.